Economic costs due to workers' sick leave at wastewater treatment plants in Bulgaria - Elka Ilieva Toseva; Rumyana Stoyanova; Tanya Turnovska (Nofer Institute of Occupational Medicine, 2018)
Background The compensatory mechanisms of social security include expenses for sick leave. The aim of the study is to determine the economic cost due to sick leave among workers in wastewater treatment plants (WWTPs), comparing with the same economic indicators of the National Social Security Institute (NSSI) in Bulgaria. Material and Methods The sick leave of 111 workers at 3 WWTPs was studied in the period 2012-2014 on the grounds of registered absences from work due to temporary incapacity for work. The economic indicators of the NSSI, the gross salary at WWTPs, payable social security contributions and compensatory payments for sick leave have been used for economic cost calculation for temporary incapacity of the workers. Results The frequency of cases and the frequency of lost days due to temporary incapacity were increased in the observed period at WWTPs and in Bulgaria, and it is significantly higher for the employed at WWTPs. The percentage share of workers equivalent to 1.66% at WWTPs have not worked for an entire year as a result of temporary incapacity in 2012, 2.76% - in 2013, and 4.61% - in 2014. The economic burden due to sick leave at WWTPs was raised from EUR 4913.02 in 2012 to EUR 16 895.80 for 2014 for employers and the NSSI. Conclusions The frequency of cases and the frequency of lost days due to temporary incapacity were increased in the observed period at WWTPs and in Bulgaria, and it is significantly higher for the employed at WWTPs. The economic burden was equally distributed between employers and the NSSI. Med Pr 2018;69(2):129-141